An economists' manifesto on unemployment in the European Union - Franco Modigliani; Jean-Paul Fitoussi; Beniamino Moro; Dennis J. Snower; Robert M. Solow; Alfred Steinherr; Stefano Sylos Labini (Quarterly review, 1998)
This manifesto challenges a pernicious orthodoxy that has gripped Europe's policy makers. It is that demand- and supply-side policies must have different aims, that a limited number of supply-side policies are to be devoted to fighting unemployment, and that demand management (and particularly monetary policy) is are to be devoted solely to fighting inflation. The prevailing orthodoxy also claims that the choice of policy instruments for combating unemployment is a political decision, in which each instrument is evaluated on a case-by-case basis. In what follows, we outline various practical proposals aimed at a prompt reduction of unemployment. We are confident that if the advice is given proper attention by governments and monetary authorities, unemployment can be reduced significantly in a matter of a few years. We will divide the proposed actions into those bearing on the revival of aggregate demand (demand policies) and those addressed to the reform of the labour and product markets and the system of benefits for the unemployed (supply policies). But we stress from the very beginning that we regard our proposals as strictly complementary with one another. Each proposal, applied in isolation, may produce little or even perverse effects, while the simultaneous application can be counted upon to yield the desired outcome. This holds in particular with respect to the relation between demand and supply policies. The underlying idea is that it is much easier to encourage people to look for jobs if there are jobs to be found and it is much easier to encourage firms to offer more jobs if there are people looking for jobs.
Keywords: 330; Beschäftigungspolitik; Arbeitslosigkeit; EU-Staaten